Clinico-microbiological study of community acquired and health care associated methicillin-resistant Staphylococcus aureus from skin and soft tissue infections - John, Swapna Helen; Lelitha, Sarada Devi Karunakaran; Surendran, Remadevi (International Journal of Research in Medical Sciences, 2017)
Background: Methicillin-resistant Staphylococcus aureus (MRSA) has long been a problematic pathogen, confined largely to hospitals and health care environments. But in the past decade, resistant strains have begun to appear among healthy community members without the traditional health care associated risk factors. In the present study, we sought to determine the prevalence of community acquired MRSA (CA-MRSA) and health care associated MRSA (HA-MRSA) among patients with skin and soft tissue infections (SSTIs ) and to study the differences between these with respect to clinical features, risk factors and antibiotic sensitivity patterns. Methods: 100 consecutive Staphyococcus aureus isolates from each from community acquired and health care associated SSTIs (a total of 200 isolates) were studied. Standard identification protocols were employed and antibiotic susceptibility testing was interpreted according to CLSI guidelines. Results: The prevalence of HA- MRSA was 54% while that of CA- MRSA was 52%. Majority of the HA-MRSA infections occurred in patients with extremes of age. In contrast, majority of CA-MRSA patients were young children. History of hospitalization in the past one year and a history of surgery in the past three months were the significant risk factors for acquiring HA-MRSA. CA-MRSA found no significant association with the known risk factors. Though the antibiotic resistance to Cotrimoxazole, Erythromycin and Clindamycin were lower among CA-MRSA isolates when compared with HA-MRSA isolates (55.8% versus 85.2%; 76.9% versus 92.6 %; 19.3% versus 29.7%), the rates of resistance of CA-MRSA isolates to non β-lactam antibiotics were higher than expected. Conclusions: CA-MRSA strains are equally prevalent as HA-MRSA strains and can no longer be lightly regarded in the current scenario. Moreover the susceptibility of CA-MRSA strains to non β lactam antibiotics seem to be decreasing and can no longer be used as defining criteria to differentiate them from HA- MRSA strains.